1998
DOI: 10.1038/1294
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the gene encoding human TTF-2 associated with thyroid agenesis, cleft palate and choanal atresia

Abstract: Congenital hypothyroidism occurs in one of every three to four thousand newborns, owing to complete or partial failure of thyroid gland development. Although thyroid hypoplasia has recently been associated with mutations in the thyrotropin (TSH) receptor, the cause of thyroid agenesis is unknown. Proteins including thyroid transcription factors 1 (TTF-1; refs 4,5) and 2 (TTF-2; refs 6,7) and Pax8 (refs 8,9) are abundant in the developing mouse thyroid and are known to regulate genes expressed during its differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(219 citation statements)
references
References 29 publications
4
206
0
7
Order By: Relevance
“…The phenotype of patients affected by Bamforth syndrome, that includes atresia of choanae and spiky hair (Clifton-Bligh et al, 1998), is consistent with the expression pattern of TTF-2 in choanae and hair follicles. The same phenotype was not reported in the titf2 null mice.…”
Section: Ttf-2 Expression In Ectoderm and Ectodermderived Structuressupporting
confidence: 67%
See 1 more Smart Citation
“…The phenotype of patients affected by Bamforth syndrome, that includes atresia of choanae and spiky hair (Clifton-Bligh et al, 1998), is consistent with the expression pattern of TTF-2 in choanae and hair follicles. The same phenotype was not reported in the titf2 null mice.…”
Section: Ttf-2 Expression In Ectoderm and Ectodermderived Structuressupporting
confidence: 67%
“…Gene targeting experiments have demonstrated that titf2/foxe1 null mice exhibit cleft palate and either a sublingual or completely absent thyroid gland (De Felice et al, 1998). In humans, mutations of the gene encoding for TTF-2 result in the Bamforth syndrome, characterized by thyroid agenesis, cleft palate, spiky hair, and choanal atresia (Clifton-Bligh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…23 The importance of these three transcription factors is evidenced by congenital thyroid agenesis, which results from mutations in any of the transcription factors. [26][27][28][29][30][31][32] We found consistent nuclear expressions of Pax8, TTF-1, and TTF-2 in well-differentiated neoplasms of follicular cell origin, that is, papillary carcinomas, follicular adenomas, follicular carcinomas, and poorly differentiated carcinomas. Seventy-nine percent of anaplastic carcinomas variably showed Pax8 reaction, whereas TTF-1 and TTF2 were expressed in only 18 and 7% of anaplastic carcinomas, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…PAX8-NKX2-1 cotransfection experiments were performed with 130 ng of PAX8 [Vilain et al, 2001] and 130 ng of NKX2-1. Transfection efficiency was normalized with 150 ng of plasmid Bosβ-gal [Clifton-Bligh et al, 1998]. After 48 hours, the cells were harvested, and luciferase (Firefly and Renilla) and β-gal assays were performed.…”
Section: Cell Culture and Transactivation Experimentsmentioning
confidence: 99%